Patient reported outcome measures in children and adolescents with type 1 diabetes using advanced hybrid closed loop insulin delivery - Gianini, Ana; Suklan, Jana; Skela-Savič, Brigita; Klemencic, Simona; Battelino, Tadej; Dovc, Klemen; Bratina, Nataša (Frontiers in Endocrinology, 2022)
Purpose To determine the impact of advanced hybrid closed - loop (AHCL) insulin delivery on quality of life, metabolic control and time in range (TIR) in youth with type 1 diabetes mellitus (T1DM). Methods Twenty-four children and adolescents with T1DM (14 female) aged of 10 to 18 years participated in the study. Mixed methods study design was implemented. Quantitative part of the study was conducted as a longitudinal crossover study with data collection before and at the end of AHCL use. Qualitative data were obtained with modeled interviews of four focus groups before and the end of the period. Clinical data were collected from the electronic medical records. Results The use of AHCL significantly improved the quality of life in terms of decreased fear of hypoglycemia (p<0.001), decrease in diabetes-related emotional distress (p<0.001), and increased wellbeing (p=0.003). The mean A1C decreased from 8.55 % (69.9 mmol/mol) (± 1.34) to 7.73 % (61.0 mmol/mol) (± 0.42) (p=0.002) at the end of the study. Mean TIR was 68.22 % (± 13.89) before and 78.26 (± 6.29) % (p<0.001) at the end of the study. Conclusion The use of advanced hybrid closed loop significantly improved the quality of life and metabolic control in children and adolescents with T1DM.